Teacher Performance Assessment in Improving Professionalism and Learning Quality - Asep Supriyadi; M. Ryan Fauzi; Shafwa Imala; Yasmi Nur Almi Permadi (Kasyafa: Jurnal Pendidikan Agama Islam, 2025)
Teacher performance assessment is an important aspect in the education system which aims to improve professionalism and the effectiveness of learning in schools. Teachers who have good performance will be able to create a conducive learning atmosphere and encourage student activity and participation in the learning process. This research discusses three main aspects in teacher performance appraisal, namely: (1) the meaning of teacher performance appraisal, (2) requirements, principles and aspects that must be considered in performance appraisal, and (3) procedures for implementing teacher performance appraisal. The method used in this research is a qualitative approach with literature study and document analysis related to teacher performance assessment policies. The results of the study show that teacher performance assessment has the main function of measuring teacher professional, pedagogical, social and personality competencies. In addition, assessments carried out systematically and based on evidence can help teachers improve their competence through training and continuous professional development. Therefore, clear and systematic procedures are needed in carrying out assessments, starting from planning, observation, analysis of results, to follow-up in the form of training and coaching for teachers. With an effective performance assessment system, it is hoped that teacher professionalism can increase and have a positive impact on the quality of learning in schools.